A Five-Helix-Based SARS-CoV-2 Fusion Inhibitor Targeting Heptad Repeat 2 Domain against SARS-CoV-2 and Its Variants of Concern - Lixiao Xing; Xinfeng Xu; Wei Xu; Zezhong Liu; Xin Shen; Jie Zhou; Ling Xu; Jing Pu; Chan Yang; Yuan Huang; Lu Lu; Shibo Jiang; et al. (Viruses, 2022)
The prolonged duration of the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) pandemic has resulted in the continuous emergence of variants of concern (VOC, e.g., Omicron) and variants of interest (VOI, e.g., Lambda). These variants have challenged the protective efficacy of current COVID-19 vaccines, thus calling for the development of novel therapeutics against SARS-CoV-2 and its VOCs. Here, we constructed a novel fusion inhibitor-based recombinant protein, denoted as 5-Helix, consisting of three heptad repeat 1 (HR1) and two heptad repeat 2 (HR2) fragments. The 5-Helix interacted with the HR2 domain of the viral S2 subunit, the most conserved region in spike (S) protein, to block homologous six-helix bundle (6-HB) formation between viral HR1 and HR2 domains and, hence, viral S-mediated cell–cell fusion. The 5-Helix potently inhibited infection by pseudotyped SARS-CoV-2 and its VOCs, including Delta and Omicron variants. The 5-Helix also inhibited infection by authentic SARS-CoV-2 wild-type (nCoV-SH01) strain and its Delta variant. Collectively, our findings suggest that 5-Helix can be further developed as either a therapeutic or prophylactic to treat and prevent infection by SARS-CoV-2 and its variants.